Pengaruh Ekstrak Daun Annona muricata L. Terhadap Ekspresi Caspase 3 Pada Adenokarsinoma Mamma Mencit C3H - Hikmah Fitriani; Ruri Eka Maryam; Tissa Octavira Permatasari (Tunas Medika Jurnal Kedokteran & Kesehatan, 2015)
Background :Treatment of breast cancer such as surgery, radiotherapy and chemotherapy still has a lot of sideeffects. This can be minimized by using herbal medicine such as Annona muricata L. which works selectively attacking cancer cells.Objective :The aim for this research was to determine effect of Annona muricata L. leaves extract on the caspase 3 expression on adenocarcinoma mammae in C3H mice.Methods : Animalexperiment using Post Test Only Control Group design was done. Twelve C3H mice were inoculted with tumour and were devided into two groups : Control (C) group and the other group was Treatment (T) group with Annona muricata L. leaves extract of dose 1 mg/day. All of the groups were treated for three weeks and then measuring caspase 3 expressi on. Mann Whitney test was conducted to analyze the data.Result : There were significant differences on the caspase 3 expression between control group compared with one group administrated with Annona muricata L. leaves extract of dose 1 mg/day respectively ( p = 0,004) between control group compared with one group administrated with Annona muricata L. leaves extract of dose 1 mg/day( p = 0,004). From the result, median of caspase 3 expression were increased with Control = 0,4 and Treatment = 1,36.Conclution :Annona muricata L. leaves extract can increase caspase 3 expressionKeywords:Annona muricata L. leaves extract, caspase 3, adenocarcinoma mammae